Reengineering the Digital Attendance System using Business Process Reengineering Approach at PT. Esa Solusi Mandiri (ESACO) - Wijdaniah, Jauza; Suharso, Wildan (P3M Politeknik Negeri Bengkalis, 2026)
This study aims to analyze and redesign the employee attendance process at PT Esa Solusi Mandiri, which is still conducted manually using paper-based forms and Microsoft Excel recapitulation. The Business Process Reengineering (BPR) approach is applied to identify value-added and non-value-added activities within the attendance process. Data were collected through semi-structured online interviews with one key informant responsible for attendance management, as well as documentation in the form of monthly attendance reports. The duration of each process stage was estimated based on interview results and administrative document analysis, resulting in a total cycle time of 190 minutes for the manual attendance process. Process efficiency was evaluated using Throughput Efficiency (TE) as an indicator of the proportion of value-added time. Based on this analysis, a conceptual design of a digital attendance process was developed, incorporating automated recording and real-time data access for HR and Finance departments. The results indicate that the proposed digital process has the potential to reduce the cycle time to 11 minutes and increase the TE value from 23.68% to 81.82%. These findings represent the potential improvement in administrative efficiency, given that the proposed digital process has not yet been implemented or tested in real operational conditions.